A Proposal of methodological steps for the diagnosis of motor abilities in the Physical Education - Marilín Páez Basabe (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2016)
Within the teaching process of Physical Education and its cardinal evaluation, the diagnosis is an essential part of its main stages, because it reveals the real situation of each student, so that the teacher can adjust his influences to their needs, constituting an important element to take into account to achieve the objectives of the educational activity since the very beginning. The present work meets the goal of designing methodological steps favoring the evaluation of the motor skills and the monitoring of lessons. It is based on the technological claims in the territory under study and the need to improve the work in the teaching process of Physical Education. Through this work the author intends to encourage the scientific methodological level of teachers and thereby increasing the quality in the development of this process. To get this aim, theoretical and empirical methods were used, including observation and survey. It facilitates a deep analysis of the problem as well as the design of the proposal. As an outcome and after an expert consult, the author presents a set of methodological steps for the running of a diagnosis on motor skills in the different levels of education. It has also served as an important tool     to the teachers of this discipline in the territory   on behalf of the subject Physical Education